English Teacher’s Code Switching in The Classroom (A Case Study in Grade IX of SMK 10 Padang) - Putri, Dian Mega (FKIP-Universitas Riau, 2020)
This research aims to reveal the attitudes of the teacher in using code switching in the classroom from English (or shorten by L2) to the Indonesian language (or shorten by L1) or vice versa and also to find out the functions of teacher’s switching to the L1 in practice in Grade IX of SMK 10 Padang. The descriptive qualitative research method is used to analyze teachers’ code switching to Indonesian language through the observation and interview. The subject in this research is an English teacher who taught in grade IX of SMK 10 Padang. Based on the analysis of the data, it can be concluded that the code switching used by the teacher in the classroom plays a positive role in the process of teaching and learning. Moreover, the functions of code switching used by the teacher in the classroom are in order to explain vocabulary, give grammar instruction, emphasize some points, manage the class, index a stance of empathy or solidarity towards students.